RANCANGAN SISTEM INFORMASI ADMINISTRASI LOGISTIK DI PT. COCA COLA SERANG - Masum Masum; Rizki Fatullah; Ely Nuryani (Journal of Innovation And Future Technology (IFTECH), 2021)
A reliable system in the company said, if the system is able to provide consumers with good quality. In addition the satety to humans and the equipment installed from the possibility of interference white the system reliability is also a requirement of a system in the company. Procurement of goods in PT.Coca-Cola is to know and understand the stock movement report (SMR) by making a request (consumer data) and with the documents submitted to the shipper. Then be made to the report. Procurement process from start stock movement report (SMR) with (consumer data) and (data placement) there will be good cooperation, so as to create mutual benefits and minimize the losses that will happen, but still there are constraints such as the accumulation of data, so that often there is less precision in data input goods, and Warehouse data which can lead to duplicate data. Problem-solving process procurement of goods, can be improved by optimizing the schedule of the procurement process, increase effectiveness and efficiency in the procurement process and create an SMR report timely and accurate.